"تأثير الرش الورقي بالبورون والزنك في الغلة وبعض مكوناتها في صنف الفول البلدي Vicia faba L. - سلامة, سليمان; حيدر, علي; أحمد, طارق (Latakia University Journal -Biological Sciences Series, 2016)
أجريت تجربة ضمن أصص بلاستيكية في الساحل السوري (قرية الهنادي)على نبات الفول البلدي (Vicia fabaL.)، لدراسة تأثير التسميد بالبورون والزنك رشاً على المجموع الخضري فردياً وبالتشارك معاً وبمعدلات متصاعدة (0، 0.25، 0.50، 0.75، و1 كغ بورون/هكتار على شكل حمض البوريك، والزنك بمعدل 0، 0.375، 0.750، 1.125، و1.5 كغ/هكتار على شكل سلفات الزنك)، حيث زرع الفول في أصص بلاستيكية ( سعة 15ليتر)(10/11/2013) و(10/11/2014) في تربة عالية المحتوى بكربونات الكالسيوم، وفقيرة بالبورون والزنك، وذات pH مائل للقاعدية (ممثلة لترب المنطقة).تم رش نصف كميات أسمدة البورون والزنك بعد مرور 33 يوماً من الإنبات، والنصف الآخر بعد مرور 65 يوماً من الإنبات، وقد أظهرت النتائج استجابات معنوية في جميع المؤشرات المدروسة (عدد الأفرع، عدد القرون في النبات، ، وزن 100 بذرة، الإنتاجالكلي من البذور(طن/ هكتار) لدى نبات الفول، نتيجة للتسميد الورقي بالبورون والزنك.كانت استجابة الفول للبورون أعلى من استجابته للزنك في جميع المؤشرات المدروسة، وكانت المعاملةB75Zn75(0.750كغمن حمض البوريك و1.125 كغ سلفات الزنك) هي الأفضل قياسا بالمعاملات الأخرى، وأدت إلى زيادة الغلة البذرية بحوالي 17.66%.the experiment was conducted under Syrian coastal conditions to investigate (Vicia fabaL.), the effect of boron and zinc foliar fertilization on faba bean,either individually or in combination, by increased rates (0, 0.25, 0.50, 0.75, and 1 kg boron / has boric acid, and zinc at a rate of 0, 0.375, 0.750, 1.125, and 1.5 kg / ha as zinc sulfate). where fababeans were plantedin plastic pots(15L) in(10/11/2013) and (10/11/2014).The soil in pots has high content of calcium carbonate, low boron and zinc content, with pH slightly basic (representative of the region's soils). Half boron and zinc fertilizer rates were sprayed after 33 days of germination and the other half ,after 65 days of germination. The results showed significant responses in all studied parameters (number of branches,number of pods / plant, weight of 100 seeds, and seed yield (Kg. / ha) on faba bean plant, as a result of foliar fertilization by boron and zinc.Fababeans response to boron is higher than to zinc fertilization in all studied indicators. However,the treatmentB75Zn75(0.75 kg boric acid and 1.125kg of zinc sulfate) is the best, as compared to others. Also, the driedseeds yield was increased by about 17.66%.